Binder and preparation method thereof, negative electrode slurry, negative electrode pole piece and lithium ion battery

By using specific polymeric monomers and branched monomers, the coating and bonding ability of the negative electrode material of lithium-ion battery is improved, the electrochemical performance loss caused by negative electrode expansion is solved, and the high-temperature circulation and storage performance of the battery is improved.

CN119875544APending Publication Date: 2025-04-25BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411848911.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The repeated expansion of the negative electrode during charging and discharging of lithium-ion batteries leads to loss of electrochemical performance, which in turn affects high-temperature cycle and storage performance.

Method used

Specific polymeric monomers and branched monomers are used to prepare binders to control the branching degree of binders and improve their ability to cover and bond to negative electrode active materials and conductive materials.

Benefits of technology

It effectively alleviates the electrochemical performance loss caused by repeated expansion of the negative electrode during the charging and discharging of the battery cell, and improves the high-temperature cycling and storage performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005191314620000121
    Figure BDA0005191314620000121
  • Figure BDA0005191314620000131
    Figure BDA0005191314620000131
  • Figure BDA0005191314620000141
    Figure BDA0005191314620000141
Patent Text Reader

Abstract

The invention discloses a binder and a preparation method thereof, negative electrode slurry, a negative electrode pole piece and a lithium ion battery. The binder comprises a polymeric monomer and a branched monomer, and the polymeric monomer comprises one or more of an acrylic acid monomer, an acrylonitrile monomer and an acrylamide monomer; and the branching degree of the binder is 0.2 C / 1000 C to 1 C / 1000 C. The specific polymeric monomer and the branched monomer are adopted to control the branching degree of the binder, so that the coating and bonding capability of the binder on a negative electrode active material and a conductive material is improved, and the electrochemical performance loss caused by repeated expansion of a negative electrode in the charging and discharging process of a battery cell is effectively relieved; and the improvement of high-temperature circulation and storage performance of the battery cell is realized. The binder also has multiple functions and can replace a binder system using CMC and SBR at the same time, and an auxiliary agent system is simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a binder and a preparation method thereof, a negative electrode slurry, a negative electrode sheet, a lithium ion battery, and an electrical device. Background Art

[0002] Lithium-ion batteries have been widely used in many fields due to their high energy density, high output voltage, fast charge and discharge, environmental protection, pollution-free and long cycle life. During the charge and discharge process of lithium-ion batteries, the electrodes often shrink and expand in volume. The repeated expansion of the negative electrode will cause the loss of electrochemical performance, resulting in poor high-temperature cycle and storage performance of the battery. Therefore, it is necessary to improve the high-temperature cycle and storage performance of lithium-ion batteries. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a binder, which can improve the high temperature cycle performance and high temperature storage performance of lithium ion batteries when applied to lithium ion batteries.

[0004] Specifically, the first aspect of the present invention provides a binder, including polymerized monomers and branched monomers, wherein the polymerized monomers include one or more of acrylic monomers, acrylonitrile monomers and acrylamide monomers; the degree of branching of the binder is 0.2C / 1000C to 1C / 1 000C.

[0005] The present invention adopts specific polymer monomers and branched monomers to control the branching degree of the binder, thereby improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieving the improvement of the high-temperature cycle and storage performance of the battery cell.

[0006] In addition, the binder of the present invention is a multifunctional binder having the functions of coating, dispersing, thickening and bonding, and can replace the binder system using carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) at the same time, thereby simplifying the auxiliary agent system.

[0007] According to some embodiments of the present invention, the degree of branching of the binder is 0.5C / 1000C to 1C / 1000C. Optimizing the degree of branching of the binder is conducive to further improving the coating, dispersion, thickening and other functions of the binder, and improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material.

[0008] According to some embodiments of the present invention, the polymerizable monomers include acrylic acid monomers, acrylonitrile monomers and acrylamide monomers. Using acrylic acid monomers, acrylonitrile monomers and acrylamide monomers at the same time is conducive to improving the coating and bonding ability of the adhesive.

[0009] According to some embodiments of the present invention, the acrylic monomer includes one or more of acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; the acrylonitrile monomer includes one or more of acrylonitrile and dimethylaminoacrylonitrile; the acrylamide monomer includes one or more of acrylamide, N-isopropylacrylamide, N-phenylacrylamide, diacetoneacrylamide and N-hydroxymethylacrylamide. Optimizing the types of polymerizable monomers is conducive to obtaining an adhesive with good coating bonding ability.

[0010] According to some embodiments of the present invention, the branching monomer includes one or more of trimethylolpropane, citric acid, phytic acid, thiourea, and pentaerythritol. Using branching monomers to control the degree of branching is within the scope of the present invention, which is beneficial to improving the coating, dispersion, thickening and other effects of the binder, and improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material.

[0011] According to some embodiments of the present invention, the weight average molecular weight of the binder is 600,000 Daltons to 1,000,000 Daltons. Controlling the molecular weight of the binder within the scope of the present invention is conducive to improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieving the improvement of the high temperature cycle and storage performance of the battery cell.

[0012] According to some embodiments of the present invention, the weight average molecular weight of the binder is 650,000 Daltons to 800,000 Daltons. Optimizing the molecular weight of the binder is conducive to further improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material.

[0013] The second aspect of the present invention provides a method for preparing the binder of the first aspect of the present invention, comprising the following steps:

[0014] reacting the polymerization monomers to obtain a polymer;

[0015] The branching monomer is grafted onto the polymer to obtain the binder.

[0016] The method of the invention has a simple process flow and mild reaction conditions and is suitable for industrial large-scale production.

[0017] According to some embodiments of the present invention, the molar ratio of the acrylic monomer, acrylonitrile monomer, and acrylamide monomer is (1-7): (2-8): (0-2). Optimizing the molar ratio of the acrylic monomer, acrylonitrile monomer, and acrylamide monomer is beneficial to improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and realizing the improvement of the high temperature cycle and storage performance of the battery cell.

[0018] According to some embodiments of the present invention, the molar ratio of the acrylic acid monomer, the acrylonitrile monomer, and the acrylamide monomer is (1-7): (2-8): (0.2-2). The acrylic acid monomer, the acrylonitrile monomer, and the acrylamide monomer are used in combination in a specific ratio, and combined with a specific degree of branching, which is conducive to further improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and realizing the improvement of the high temperature cycle and storage performance of the battery cell.

[0019] According to some embodiments of the present invention, the molar ratio of the acrylic acid monomer, acrylonitrile monomer, and acrylamide monomer is (2.5-4.5): (5-6.5): (0.5-1.5). Optimizing the usage ratio of acrylic acid monomer, acrylonitrile monomer, and acrylamide monomer is beneficial to further enhance the coating and bonding ability of the binder to the negative electrode active material and the conductive material.

[0020] The third aspect of the present invention provides a negative electrode slurry, comprising the binder of the first aspect of the present invention or the binder obtained by the method of the second aspect of the present invention. Due to the use of the binder of the present invention, the negative electrode slurry of the present invention can also effectively alleviate the electrochemical performance loss caused by repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieve the improvement of the high temperature cycle and storage performance of the battery cell.

[0021] According to some embodiments of the present invention, the Zeta potential of the negative electrode slurry is -55mV to -.80mV. Controlling the Zeta potential of the negative electrode slurry within the scope of the present invention can effectively regulate the adsorption of the binder on the surface of the negative electrode active material and the conductive material, thereby facilitating the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieving the improvement of the high temperature cycle and storage performance of the battery cell.

[0022] According to some embodiments of the present invention, the negative electrode slurry further includes a negative electrode active material and a conductive material; the mass ratio of the binder to the negative electrode active material is 0.5:100 to 5:100. Optimizing the amount of the binder is conducive to improving the stability and adhesion of the slurry, thereby effectively alleviating the electrochemical performance loss caused by repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and improving the high temperature cycle and storage performance of the battery cell.

[0023] The fourth aspect of the present invention provides a negative electrode plate, comprising the binder of the first aspect of the present invention or the binder obtained by the method of the second aspect of the present invention. Due to the use of the binder of the present invention, the negative electrode plate of the present invention can also effectively alleviate the electrochemical performance loss caused by repeated expansion of the negative electrode during the charging and discharging process of the battery cell, and achieve the improvement of the high temperature cycle and storage performance of the battery cell.

[0024] According to some embodiments of the present invention, the peel strength of the negative electrode sheet is 4.0N / m-9.5N / m. Optimizing the peel strength of the negative electrode sheet is beneficial to reducing the risk of the active material layer falling off from the negative electrode current collector and improving the high temperature cycle and storage performance of the battery cell.

[0025] The fifth aspect of the present invention provides a lithium ion battery, comprising the negative electrode sheet of the fourth aspect of the present invention. Due to the use of the binder of the present invention, the electrochemical performance loss caused by repeated expansion of the negative electrode during the charge and discharge process of the battery cell can be effectively alleviated, and the high temperature cycle and storage performance of the battery cell can be improved.

[0026] The sixth aspect of the present invention provides an electrical device, comprising the lithium ion battery of the fifth aspect of the present invention. Due to the use of the binder of the present invention, the electrochemical performance loss caused by repeated expansion of the negative electrode during the charge and discharge process of the battery cell can be effectively alleviated, and the high temperature cycle and storage performance of the battery cell can be improved.

[0027] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0028] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0029] In the description of the present invention, unless otherwise specified, "plurality" means two or more. "Multiple" means two or more. In this article, the term "comprising" or "including" is an open expression, that is, including the content specified in the present invention, but does not exclude other aspects.

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] Lithium-ion batteries have been widely used in many fields due to their high energy density, high output voltage, fast charge and discharge, environmental protection, pollution-free and long cycle life. During the charge and discharge process of lithium-ion batteries, the electrodes often shrink and expand in volume. The repeated expansion of the negative electrode will cause the loss of electrochemical performance, resulting in poor high-temperature cycle and storage performance of the battery. Therefore, it is necessary to improve the high-temperature cycle and storage performance of lithium-ion batteries.

[0032] The binder in the negative electrode plate can bond and retain the negative electrode active material, strengthen the contact between the negative electrode active material and the conductive agent, and at the same time, can bind the negative electrode active material to the current collector to prevent it from falling off. By optimizing the binder in the negative electrode plate and improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charging and discharging of the battery cell can be effectively alleviated, and the high-temperature cycle and storage performance of the battery cell can be improved. Based on this, the present invention provides a binder, which improves the coating and bonding ability of the binder to the negative electrode active material and the conductive material by adopting a specific polymerized monomer and a branched monomer to control the branching degree of the binder, and finally achieves the improvement of the high-temperature cycle and storage performance of the battery cell.

[0033] Specifically, the first aspect of the present invention provides a binder, including polymerized monomers and branched monomers, wherein the polymerized monomers include one or more of acrylic monomers, acrylonitrile monomers and acrylamide monomers; the degree of branching of the binder is 0.2C / 1000C to 1C / 1000C.

[0034] The binder of the present invention is also a multifunctional water-based binder, which has coating, dispersing, thickening and bonding functions, and can replace the binder system using sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) at the same time, thereby simplifying the auxiliary agent system.

[0035] The binder of the present invention comprises a main chain formed by polymerization of polymerizable monomers, and a branched chain formed by grafting a branched monomer onto the main chain. In the present invention, the degree of branching represents the number of carbon atoms grafted per 1000 carbon atoms. For example, "1C / 1000C" represents that 1 carbon atom is grafted per 1000 carbon atoms, or in other words, 1 carbon atom is grafted with a branched monomer per 1000 carbon atoms, or in other words, 1 carbon atom is grafted with a branched monomer per 1000 carbon atoms.

[0036] In some embodiments, the degree of branching of the binder may be 0.5C / 1000C to 1C / 1000C. Optimizing the degree of branching of the binder is beneficial to further enhance the coating, dispersion, thickening and other functions of the binder, and enhance the coating and bonding ability of the binder to the negative electrode active material and the conductive material.

[0037] In some specific embodiments, the degree of branching of the binder may be 0.5C / 1000C, 0.6C / 1000C, 0.7C / 1000C, 0.8C / 1000C, 0.9C / 1000C or 1C / 1000C.

[0038] In some embodiments, the polymerizable monomers include acrylic acid monomers, acrylonitrile monomers and acrylamide monomers. Using acrylic acid monomers, acrylonitrile monomers and acrylamide monomers at the same time is conducive to improving the coating and bonding ability of the adhesive.

[0039] In some embodiments, the acrylic monomer includes one or more of acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; the acrylonitrile monomer includes one or more of acrylonitrile and dimethylaminoacrylonitrile; the acrylamide monomer includes one or more of acrylamide, N-isopropylacrylamide, N-phenylacrylamide, diacetoneacrylamide and N-hydroxymethylacrylamide. Optimizing the types of polymerizable monomers is conducive to obtaining an adhesive with good coating bonding ability.

[0040] In some embodiments, the branching monomer includes one or more of trimethylolpropane, citric acid, phytic acid, thiourea, and pentaerythritol. Using branching monomers to control the degree of branching is within the scope of the present invention, which is beneficial to improving the coating, dispersion, thickening and other effects of the binder, and improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material. The hydroxyl group in pentaerythritol can react with the carboxyl group in the acrylic acid monomer to achieve grafting. The amino group in thiourea can react with the carboxyl group in the acrylic acid monomer to achieve grafting. The phosphate group in phytic acid can react with the carboxyl group in the acrylic acid monomer to achieve grafting. The hydroxyl group in citric acid can react with the carboxyl group in the acrylic acid monomer to achieve grafting. The hydroxyl group in trimethylolpropane can react with the carboxyl group in the acrylic acid monomer to achieve grafting.

[0041] In some embodiments, the weight average molecular weight of the binder may be 600,000 Daltons to 1,000,000 Daltons. Controlling the molecular weight of the binder within the scope of the present invention is conducive to improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieving the improvement of the high temperature cycle and storage performance of the battery cell.

[0042] In some specific embodiments, the weight average molecular weight of the binder may be 650,000 Daltons to 800,000 Daltons. Optimizing the molecular weight of the binder is conducive to further improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material.

[0043] In some specific embodiments, the weight average molecular weight of the binder can be 600,000 Daltons, 650,000 Daltons, 700,000 Daltons, 750,000 Daltons, 800,000 Daltons, 850,000 Daltons, 900,000 Daltons, 950,000 Daltons, or 1,000,000 Daltons.

[0044] The second aspect of the present invention provides a method for preparing the binder of the first aspect of the present invention, comprising the following steps:

[0045] reacting the polymerization monomers to obtain a polymer;

[0046] The branching monomer is grafted onto the polymer to obtain the binder.

[0047] The method of the invention has a simple process flow and mild reaction conditions and is suitable for industrial large-scale production.

[0048] In some embodiments, the molar ratio of the acrylic acid monomer, acrylonitrile monomer, and acrylamide monomer may be (1-7): (2-8): (0-2). Optimizing the molar ratio of the acrylic acid monomer, acrylonitrile monomer, and acrylamide monomer is beneficial to improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieving the improvement of the high temperature cycle and storage performance of the battery cell.

[0049] In some embodiments, the molar ratio of the acrylic acid monomer, acrylonitrile monomer, and acrylamide monomer can be (1-7): (2-8): (0.2-2). The acrylic acid monomer, acrylonitrile monomer, and acrylamide monomer are used in combination in a specific ratio, and combined with a specific degree of branching, which is conducive to further improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and realizing the improvement of the high temperature cycle and storage performance of the battery cell.

[0050] In some specific embodiments, the molar ratio of the acrylic monomer, the acrylonitrile monomer, and the acrylamide monomer may be (1.5-6.5):(2.5-7.5):(0.2-1.8), (2-6):(3-7):(0.5-1.5), (2.5-5.5):(3.5-6.5):(0.5-1.5), (2.5-5):(4-6.5):(0.5-1.5), (2.5-4.5):(4.5-6.5):(0.5-1.5), (2.5-4.5):(5-6.5):(0.5-1.5), (3-4):(4.5-6):(0.7-1.3), or (3.5-4):(5-5.5):(0.9-1.1).

[0051] In some embodiments, the molar ratio of the acrylic acid monomer, acrylonitrile monomer, and acrylamide monomer may be (2.5-4.5): (5-6.5): (0.5-1.5). Optimizing the usage ratio of acrylic acid monomer, acrylonitrile monomer, and acrylamide monomer is beneficial to further enhance the coating and bonding ability of the binder to the negative electrode active material and the conductive material.

[0052] In some specific embodiments, the molar ratio of the acrylic acid monomer, the acrylonitrile monomer, and the acrylamide monomer may be 2.5:5:0.5, 2.5:5.5:0.5, 2.5:6:0.5, 2.5:6.5:0.5, 3:5:0.5, 3:5.5:0.5, 3:6:0.5, 3:6.5:0.5, 3.5:5:0.5, 3.5:5.5:0.5, 3.5:6:0.5, 3 .5∶6.5∶0.5、4∶5∶0.5、4∶5.5∶0.5、4∶6∶0.5、4∶6.5∶0.5、4.5∶5∶0.5、4.5∶5.5∶0.5、4.5∶6∶0.5、4.5∶6.5∶0.5、2.5∶5∶1、2.5∶5.5∶1、2.5∶6∶1、2.5∶6.5∶1、3∶5∶1、3∶5.5∶1、3∶6∶1、3∶6.5∶ 1、3.5∶5∶1、3.5∶5.5∶1、3.5∶6∶1、3.5∶6.5∶1、4∶5∶1、4∶5.5∶1、4∶6∶1、4∶6.5∶1、4.5∶5∶1、4.5∶5.5∶1、4.5∶6∶1、4.5∶6.5∶1、2.5∶5∶1.5、2.5∶5.5∶1.5、2.5∶6∶1.5、2.5∶6.5∶1.5、3∶5∶1.5 , 3∶5.5∶1.5, 3∶6∶1.5, 3∶6.5∶1.5, 3.5∶5∶1.5, 3.5∶5.5∶1.5, 3.5∶6∶1.5, 3.5∶6.5∶1.5, 4∶5∶1.5, 4∶5.5∶1.5, 4∶6∶1.5, 4∶6.5∶1.5, 4.5∶5∶1.5, 4.5∶5.5∶1.5, 4.5∶6∶1.5 or 4.5∶6.5∶1.5.

[0053] In some embodiments, reacting the polymerized monomers comprises: mixing a dispersion medium and an emulsifier, adding an initiator and a polymerized monomer under a protective atmosphere, and obtaining a polymer after the reaction. The dispersion medium comprises water. The present invention does not particularly limit the type of emulsifier, as long as it is an emulsifier commonly used in emulsion polymerization, such as sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate, etc. The amount of the emulsifier can be 1%-2% of the weight of the polymerized monomer. The present invention does not particularly limit the type of initiator, such as ammonium persulfate, potassium persulfate, hydrogen peroxide, azobisisobutylamidine and other water-soluble initiators. The amount of the initiator can be 0.5%-1% of the weight of the polymerized monomer. The temperature of the polymerization reaction can be 60°C-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C.

[0054] In some embodiments, grafting the branched monomer onto the polymer comprises: mixing the polymer with the branched monomer, heating and reacting to form a precursor; reacting the precursor under heating and vacuum conditions, and adding water to swell after cooling. The heating reaction temperature of the polymer and the branched monomer may be 50°C-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C; the reaction time may be 2h-4h, for example, 2h, 2.5h, 3h, 3.5h or 4h. The reaction temperature of the precursor may be 140°C-160°C, for example, 140°C, 145°C, 150°C, 155°C or 160°C; the reaction time may be 7h-9h, for example, 7h, 7.5h, 8h, 8.5h or 9h. The swelling time of adding water may be 1h-3h, for example, 1h, 1.5h, 2h, 2.5h or 3h.

[0055] The third aspect of the present invention provides a negative electrode slurry, comprising the binder of the first aspect of the present invention or the binder obtained by the method of the second aspect of the present invention. Due to the use of the binder of the present invention, the negative electrode slurry of the present invention can also effectively alleviate the electrochemical performance loss caused by repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieve the improvement of the high temperature cycle and storage performance of the battery cell.

[0056] In some embodiments, the Zeta potential of the negative electrode slurry may be -55mV to -80mV. Controlling the Zeta potential of the negative electrode slurry within the scope of the present invention can effectively regulate the adsorption of the binder on the surface of the negative electrode active material and the conductive material, thereby facilitating the coating and bonding ability of the binder on the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieving the improvement of the high temperature cycle and storage performance of the battery cell.

[0057] In some specific embodiments, the zeta potential of the negative electrode slurry can be -55 mV, -60 mV, -65 mV, -70 mV, -75 mV or -80 mV.

[0058] In some embodiments, the negative electrode slurry further includes a negative electrode active material and a conductive material. The mass ratio of the binder to the negative electrode active material may be 0.5:100 to 5:100. Optimizing the amount of the binder is conducive to improving the stability and adhesion of the slurry, thereby effectively alleviating the electrochemical performance loss caused by repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and improving the high temperature cycle and storage performance of the battery cell.

[0059] In some specific embodiments, the mass ratio of the binder to the negative electrode active material may be 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100 or 5:100.

[0060] In some embodiments, the negative electrode slurry includes a negative electrode active material, a conductive material, the binder, and water.

[0061] In some embodiments, the negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, and soft carbon. The BET specific surface area of ​​the negative electrode active material may be 0.5 m 2 / g-10m 2 / g, for example, 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g or 10m 2 / g.

[0062] In some embodiments, the conductive material includes one or more of carbon black, carbon nanotubes, conductive graphite, graphene, and carbon fiber. The BET specific surface area of ​​the conductive material may be 10-500 m 2 / g, for example, 10m 2 / g, 50m 2 / g、100m2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g or 500m 2 / g.

[0063] The fourth aspect of the present invention provides a negative electrode plate, comprising the binder of the first aspect of the present invention or the binder obtained by the method of the second aspect of the present invention. Due to the use of the binder of the present invention, the negative electrode plate of the present invention can also effectively alleviate the electrochemical performance loss caused by repeated expansion of the negative electrode during the charging and discharging process of the battery cell, and achieve the improvement of the high temperature cycle and storage performance of the battery cell.

[0064] According to some embodiments of the present invention, the peel strength of the negative electrode sheet may be 4.0 N / m-9.5 N / m. Optimizing the peel strength of the negative electrode sheet is beneficial to reducing the risk of the active material layer falling off from the negative electrode current collector and improving the high temperature cycle and storage performance of the battery cell.

[0065] In some specific embodiments, the peel strength of the negative electrode sheet may be 4.0 N / m, 4.5 N / m, 5.0 N / m, 5.5 N / m, 6.0 N / m, 6.5 N / m, 7.0 N / m, 7.5 N / m, 8.0 N / m, 8.5 N / m, 9.0 N / m or 9.5 N / m.

[0066] In the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector. The peel strength of the negative electrode sheet indicates the bonding performance between the negative electrode active layer and the negative electrode current collector. The higher the peel strength, the more difficult it is to separate the negative electrode active layer from the negative electrode current collector.

[0067] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0068] Example 1

[0069] (1) Preparation of binder

[0070] In a multi-opening glass reactor with a condensing device, 400 g of deionized water and 1.0 g of sodium dodecyl sulfate (emulsifier) ​​were added, and the mixture was heated to a constant temperature of 70° C. Nitrogen was passed through the reactor for deoxygenation for 30 min under stirring. When the temperature was stabilized at 70° C., 0.50 g of potassium persulfate (initiator) was added, and 200 g of a 12% aqueous solution of acrylic acid was added dropwise. 600 g of a 6% aqueous solution of acrylonitrile and 400 g of a 2% aqueous solution of acrylamide were compounded into an aqueous solution and then added dropwise (the molar ratio of acrylic acid, acrylonitrile and acrylamide was 3:6:1). The addition time was 4 hours, and the reaction was continued for 2 hours to obtain a polymer emulsion.

[0071] Take 100g of polymer emulsion, stir it magnetically, add 0.1g of pentaerythritol, heat it to 60°C in a water bath, and then keep it at this temperature for 3h to form a uniformly mixed precursor; react the precursor at 150°C under vacuum conditions for 8h, cool it naturally, add deionized water to swell the reaction product for 2h, and obtain a multi-branched structural adhesive.

[0072] (2) Preparation of negative electrode sheet

[0073] The BET specific surface area is 4m 2 / g of natural graphite, BET specific surface area 100m 2 / g of carbon black and the binder prepared in step (1) are mixed in a mass ratio of 100:1:1.5, added to a solvent of deionized water, and stirred evenly under the action of a vacuum stirrer to obtain a negative electrode slurry, wherein the solid content in the negative electrode slurry is 50wt%, and the Zeta potential of the negative electrode slurry is -72mV; the negative electrode slurry is evenly coated on the negative electrode collector copper foil and dried at 85°C, and then cold pressed, trimmed, cut into pieces, and slit, and finally dried under vacuum conditions at 120°C to obtain a negative electrode sheet.

[0074] (3) Preparation of positive electrode sheet

[0075] The positive electrode active material lithium iron phosphate, the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 100:1:2, added to the solvent N-methylpyrrolidone (NMP), and stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content in the positive electrode slurry is 60wt%; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil and dried at 85°C, and then cold pressed, trimmed, cut into pieces, and slit, and finally continued to be dried under vacuum conditions at 85°C to obtain a positive electrode sheet.

[0076] (4) Preparation of electrolyte

[0077] The organic solvent is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, EMC and DEC is 20:20:60. In an argon atmosphere glove box with a water content of less than 10ppm, fully dried LiPF6 is dissolved in the above organic solvent and mixed evenly to obtain an electrolyte. The concentration of LiPF6 is 1 mol / L.

[0078] (5) Diaphragm

[0079] A polyethylene film (PE) with a thickness of 14 μm was used as the separator.

[0080] (6) Preparation of lithium-ion batteries

[0081] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound into square bare cells, the pole ears are welded, and the bare cells are placed in packaging foil aluminum-plastic film, and then baked at 80°C to remove water, and then the electrolyte is injected and sealed. After that, after standing, hot and cold pressing, formation, shaping, capacity testing and other processes, a soft-package lithium-ion battery is obtained.

[0082] Example 2-22

[0083] Examples 2-22 all prepared binders and lithium-ion batteries according to the description of Example 1, with the differences shown in Table 1 below.

[0084] Comparative Example 1

[0085] The binder and lithium ion battery were prepared as described in Example 1, except that CMC and SBR were used instead of the binder prepared in step (1). The mass ratio of natural graphite, carbon black, CMC and SBR was 100:1:0.75:0.75.

[0086] Comparative Examples 2-4

[0087] Comparative Examples 2-4 all prepared binders and lithium-ion batteries according to the description of Example 1, with the differences shown in Table 1 below.

[0088] Test Method

[0089] (1) Weight average molecular weight test of binder

[0090] The weight average molecular weight of the binder was measured by gel permeation chromatography (GPC). Test method: N, N-dimethylformamide (DMF) mobile phase, concentration 3.5 mg / mL, column temperature 50° C. The test results are shown in Table 1 below.

[0091] (2) Binder branching test

[0092] The degree of branching of the binder was measured by nuclear magnetic resonance (NMR), by identifying the area 1 of the acrylic monomer signal peak and the area 2 of the branched monomer signal in the binder, and calculating (area 2 / area 1)*1.9 to obtain the degree of branching of the binder. The test results are shown in Table 1 below.

[0093] (3) Zeta potential test of negative electrode slurry

[0094] The Zeta potential of the negative electrode slurry is measured by a Zeta potential meter. Zeta potential is a tool to characterize the surface charge and charge of molecules or particles. It represents the dispersion level of particles in the medium (water). The higher the dispersion, the greater the Zeta potential (absolute value), and the more stable the system. The Z mean of the Zeta potential is usually used to represent the overall dispersion state of the system.

[0095] Zeta potential testing method:

[0096] After the instrument was turned on for 60 minutes, the test was conducted again; the negative electrode slurry was diluted with deionized water to a concentration of about 0.25wt%; the sample was then ultrasonicated or stirred to a uniform suspension; and the potential test mode was selected for the test. The test results are shown in Table 1 below.

[0097] (4) Peel strength test of negative electrode

[0098] The peel strength of the negative electrode sheet is measured by a universal material testing machine. Based on the beam bending theory of the elastic substrate, the peel strength is decomposed into the splitting force and shear stress at the peeling separation position. When the shear stress is less than the splitting force, the peel strength value can be obtained. The test results are shown in Table 1 below.

[0099] (5) High temperature cycle performance test of lithium-ion batteries

[0100] 1. Place the battery in a 60°C environment until the battery temperature reaches thermal equilibrium.

[0101] 2. Charge at 1C constant current and constant voltage to 3.7V, cut-off current 0.05C, and leave for 10 minutes;

[0102] 3. 1C constant current discharge 17.5% SOC (i.e. state of charge), leave for 10 minutes;

[0103] 4. Repeat steps 2-3 100 times;

[0104] 5. Carry out capacity test: discharge and charge twice with 1C constant current, and record the battery capacity;

[0105] 6. Repeat steps 1 to 5 until 3000 cycles. The test results are shown in Table 1 below.

[0106] (6) High temperature storage performance test of lithium-ion batteries

[0107] 1. Store the battery at 60°C;

[0108] 2. On the 60th day, place the battery in a 25°C environment until the battery temperature reaches thermal equilibrium and record the battery voltage after storage;

[0109] 3. Carry out capacity test: discharge and charge twice at 1C constant current, record the battery capacity, and calculate the capacity retention rate. The test results are shown in Table 1 below.

[0110] Table 1

[0111]

[0112]

[0113]

[0114] By comparing the examples and comparative examples in Table 1, it can be seen that the present invention uses specific polymerized monomers and branched monomers to control the branching degree of the binder, thereby improving the coating and bonding ability of the binder to the negative electrode active material and the conductive material, effectively alleviating the electrochemical performance loss caused by the repeated expansion of the negative electrode during the charge and discharge process of the battery cell, and achieving the improvement of the high-temperature cycle and storage performance of the battery cell. In addition, controlling the type and ratio of the polymerized monomers and the molecular weight of the binder can also effectively improve the coating and bonding ability of the binder, and improve the high-temperature cycle and storage performance of the battery cell.

[0115] In addition, the binder of the present invention is a multifunctional binder having the functions of coating, dispersing, thickening and bonding, and can replace the binder system using carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) at the same time, thereby simplifying the auxiliary agent system.

[0116] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0117] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A binder, characterized in that: The binder comprises polymerized monomers and branched monomers, wherein the polymerized monomers comprise one or more of acrylic acid monomers, acrylonitrile monomers and acrylamide monomers; and the branching degree of the binder is 0.2C / 1000C to 1C / 1000C.

2. The adhesive according to claim 1, characterized in that The branching degree of the binder is 0.5C / 1000C to 1C / 1000C.

3. The adhesive according to claim 1 or 2, characterized in that: The polymerizable monomers include acrylic acid monomers, acrylonitrile monomers and acrylamide monomers.

4. The adhesive according to claim 1 or 2, characterized in that: The acrylic monomers include one or more of acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; the acrylonitrile monomers include one or more of acrylonitrile and dimethylaminoacrylonitrile; the acrylamide monomers include one or more of acrylamide, N-isopropylacrylamide, N-phenylacrylamide, diacetoneacrylamide and N-hydroxymethylacrylamide.

5. The adhesive according to claim 1 or 2, characterized in that: The branching monomer includes one or more of trimethylolpropane, citric acid, phytic acid, thiourea, and pentaerythritol.

6. The adhesive according to claim 1 or 2, characterized in that: The weight average molecular weight of the binder is 600,000 Daltons to 1,000,000 Daltons.

7. The adhesive according to claim 6, characterized in that The weight average molecular weight of the binder is 650,000 Daltons to 800,000 Daltons.

8. A method for preparing the binder according to any one of claims 1 to 7, characterized in that: The following steps are involved: reacting the polymerization monomers to obtain a polymer; The branching monomer is grafted onto the polymer to obtain the binder.

9. The method according to claim 8, characterized in that The molar ratio of acrylic acid monomer, acrylonitrile monomer and acrylamide monomer is (1-7): (2-8): (0-2).

10. The method according to claim 9, characterized in that The molar ratio of the acrylic acid monomer, the acrylonitrile monomer and the acrylamide monomer is (1-7): (2-8): (0.2-2).

11. The method according to claim 10, characterized in that The molar ratio of the acrylic acid monomer, the acrylonitrile monomer and the acrylamide monomer is (2.5-4.5): (5-6.5): (0.5-1.5).

12. A negative electrode slurry, characterized in that: The invention comprises the binder according to any one of claims 1 to 7 or the binder obtained by the method according to any one of claims 8 to 11.

13. The negative electrode slurry according to claim 12, characterized in that: The zeta potential of the negative electrode slurry is -55mV to -80mV.

14. The negative electrode slurry according to claim 12 or 13, characterized in that: It also includes a negative electrode active material and a conductive material; the mass ratio of the binder to the negative electrode active material is 0.5:100 to 5:

100.

15. A negative electrode plate, characterized in that: The invention comprises the binder according to any one of claims 1 to 7 or the binder obtained by the method according to any one of claims 8 to 11.

16. The negative electrode sheet according to claim 15, characterized in that: The peel strength of the negative electrode sheet is 4.0 N / m-9.5 N / m.

17. A lithium ion battery, characterized in that: Including the negative electrode sheet as described in claim 15 or 16.

18. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 17.